In vivo Study of Uric Acid Inhibitory of Catechin from Gambir [Uncaria gambir (Hunter) Roxb] in Male Rats - Yunarto, Nanang; Ismaya, Nurwulan Adi; Reswandaru, Uud Nourma; Hermiyanti, Evika; Gumilang, Nabila Cahya; Salina, Fitri (Jurnal Kefarmasian Indonesia, 2024)
Hyperuricemia is a metabolic disease characterized by high levels of uric acid in the blood. In silico studies of catechin compounds using molecular docking were able to inhibit the activity of the xanthin oxidase enzyme so that it could reduce uric acid levels. One of the native Indonesian plants that contains catechin is gambier (Uncaria gambir (Hunter) Roxb). This research aims to obtain the efficacy and safety of gambier leaf catechins in reducing uric acid levels. In vivo efficacy testing at doses of 20, 40, and 40 mg/Kg BW with allopurinol as a comparison and the safety of gambier leaf catechin in hyperuricemic male mice through macroscopic and microscopic examination of the liver and kidney organs. The results of research on determining catechin levels using HPTLC obtained levels of 96.06%. Gambier leaf catechin at doses of 20, 40, and 40 mg/Kg BW was able to reduce uric acid levels in the blood serum of mice. The higher the dose of catechin, the better the anti-hyperuricemia effect. In the results of the safety parameters, gambier leaf catechins, there were no specific abnormalities in the liver and kidneys of mice both macroscopically and microscopically. Based on research, it can be concluded that gambier leaf catechin has great potential as an anti-hyperuricemia drug and has good safety if consumed for a long time.